Profiles of children's social–emotional health at school entry and associated income, gender and language inequalities: a cross-sectional population-based study in British Columbia, Canada. Issue 7 (26th July 2017) - Thomson, Kimberly C; Guhn, Martin; Richardson, Chris G; Ark, Tavinder K; Shoveller, Jean
Abstract : Objectives: Early identification of distinct patterns of child social–emotional strengths and vulnerabilities has the potential to improve our understanding of child mental health and well-being; however, few studies have explored natural groupings of indicators of child vulnerability and strengths at a population level. The purpose of this study was to examine heterogeneity in the patterns of young children's social and emotional health and investigate the extent to which sociodemographic characteristics were associated. Design: Cross-sectional study based on a population-level cohort. Setting: All kindergarten children attending public schools between 2004 and 2007 in British Columbia (BC), Canada. Participants: 35 818 kindergarten children (age of 5 years) with available linked data from the Early Development Instrument (EDI), BC Ministry of Health and BC Ministry of Education. Outcome measure: We used latent profile analysis (LPA) to identify distinct profiles of social–emotional health according to children's mean scores across eight social–emotional subscales on the EDI, a teacher-rated measure of children's early development. Subscales measured children's overall social competence, responsibility and respect, approaches to learning, readiness to explore, prosocial behaviour, anxiety, aggression and hyperactivity. Results: Six social–emotional profiles were identified: (1) overall high social–emotional functioning, (2) inhibited-adaptive (3) uninhibited-adaptive, (4) inhibited-disengaged, (5) uninhibited-aggressive/hyperactive and (6) overall low social–emotional functioning. Boys, children with English as a second language (ESL) status and children with lower household income had higher odds of membership to the lower social–emotional functioning groups; however, this association was less negative among boys with ESL status. Conclusions: Over 40% of children exhibited some vulnerability in early social–emotional health, and profiles were associated with sociodemographic factors. Approximately 9% of children exhibited multiple co-occurring vulnerabilities. This study adds to our understanding of population-level distributions of children's early social–emotional health and identifies profiles of strengths and vulnerabilities that can inform future intervention efforts.